First record of freshwater planarian Girardia tigrina (Platyhelminthes, Tricladida, Continenticola) in Eastern Europe - Kanana, Yuliia; Riutort, Marta (Zootaxa, 2019)
The genus Girardia Ball, 1974 houses freshwater planarian species and is the second after Dugesia Girard, 1850 within Dugesiidae regarding the number of species. It contains 45 species (Tyler et al. 2006–2019) including three recently described: one from China—Girardia sinensis Chen & Wang 2015 (Chen et al. 2015), and two cave-dwelling planarians from Brasil—Girardia desiderensis Souza & Leal-Zanchet 2016 and Girardia pierremartini Souza & Leal-Zanchet 2016 (Souza et al. 2016).